SOSIALISASI DAN INTERNALISASI DALAM PEMBELAJARAN DRUM ANAK-ANAK (Studi Kasus Pengajaran Drum di Lembaga Kursus Musik West Brothers) - Permana, Indra (Institut Seni Indonesia (ISI) Surakarta, 2018)
ABSTRACTÂ This paper begins with an interest in seeing the musical abilities of children learners of non-formal institutions of West Brothers music course in playing the drum, where the children show